2003
DOI: 10.1046/j.1468-2982.2003.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise and Plasma Beta Endorphin Levels in Patients with Migrainous Headache Without Aura

Abstract: This study aims to evaluate the effects of plasma beta endorphin level and exercise on migrainous headache. Forty patients with migrainous headache without aura (MWOA), firstly exercised on a treadmill and afterwards were asked to continue an aerobic home exercise program for six weeks. On evaluation, basal plasma beta endorphin level was negatively correlated with total duration of attacks in the last month period (P = 0.01). Exercise was found to have beneficial effects on all migraine parameters (P < 0.0001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(110 citation statements)
references
References 39 publications
3
92
1
13
Order By: Relevance
“…In addition to the prophylactic drug therapies, multiple studies have shown benefits of non-pharmacological interventions such as aerobic exercise 17,18,19,20,21,22,23,24 . Exercise of moderate intensity and practiced regularly can promotes muscle relaxation, improved cardiovascular fitness and also reduces the frequency, intensity and duration of headache attacks 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the prophylactic drug therapies, multiple studies have shown benefits of non-pharmacological interventions such as aerobic exercise 17,18,19,20,21,22,23,24 . Exercise of moderate intensity and practiced regularly can promotes muscle relaxation, improved cardiovascular fitness and also reduces the frequency, intensity and duration of headache attacks 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Hypotheses for the mechanisms by which exercise may reduce headache include decreased peripheral sensitization and activation of descending inhibitory pathways 25 . Studies where the exercise was supervised by a physical therapist demonstrated higher patient compliance 18,19,20 . However, even the studies without supervision, with exercises performed at home, positive results have been reported 20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…A prática de exercícios físicos aeróbicos regulares é considerada por alguns como forma de reduzir a freqüência das crises bem como de melhorar a qualidade de vida de seus praticantes [3][4][5][6] . Para outros, o exercício é desaconselhado pela possibilidade de deflagrar as crises de cefaléia e sintomas associados 7,8 .…”
unclassified
“…The increase in beta-endorphin levels is reported both after home exercise program and also after treadmill training. As a result, in this study, beneficial effects of the exercise was emphasized to exist especially in those patients with migraine without aura, whose basic beta-endorphin levels are low (Köseoğlu et al, 2003). In the collection study that was performed by Busch and Gaul, it was reported that there was a significant decrease in migraine attacks, pain severity, pain frequency and duration of pain, as a result of aerobic exercise programs applied on migraine patients.…”
Section: Resultsmentioning
confidence: 87%